2007
DOI: 10.1095/biolreprod.106.057554
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association, in Local Release, of Luteal Oxytocin with Endothelin 1 and Prostaglandin F2alpha During Spontaneous Luteolysis in the Cow: A Possible Intermediatory Role for Luteolytic Cascade Within the Corpus Luteum1

Abstract: Luteolysis is caused by a pulsatile release of prostaglandin F(2alpha) (PGF(2alpha)) from the uterus in ruminants, and a positive feedback between endometrial PGF(2alpha) and luteal oxytocin (OXT) has a physiologic role in the promotion of luteolysis. The bovine corpus luteum (CL) produces vasoactive substances, such as endothelin 1 (EDN1) and angiotensin II (Ang II), that mediate and progress luteolysis. We hypothesized that luteal OXT has an additive function to ensure the CL regression with EDN1 and Ang II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 44 publications
0
7
0
3
Order By: Relevance
“…This could explain why there was a tendency for P4 concentrations to increase in the present study, since the CLs of some cows were still sensitive to OXY while others were not. Shirasuna et al [23] recently confirmed this dual role of luteal OXY as luteotropic (during the early luteal and mid-luteal phases) and luteolytic (during the late luteal phase after initiation of the luteolytic cascade), highlighting the modulatory effect of OXY on local secretion of vasoactive substances within the CL.…”
Section: Discussionmentioning
confidence: 94%
“…This could explain why there was a tendency for P4 concentrations to increase in the present study, since the CLs of some cows were still sensitive to OXY while others were not. Shirasuna et al [23] recently confirmed this dual role of luteal OXY as luteotropic (during the early luteal and mid-luteal phases) and luteolytic (during the late luteal phase after initiation of the luteolytic cascade), highlighting the modulatory effect of OXY on local secretion of vasoactive substances within the CL.…”
Section: Discussionmentioning
confidence: 94%
“…Other genes that showed high downregulation were previously described to be involved in: (1) (Table 1) and Oxtr (Shirasuna et al 2007) and Prlr (Le et al 2012; see Fig. S1 and Table S1); (2) proliferation, cell cycle and apoptosis, namely Btc (Oh et al 2011), Rasl10a (Elam et al 2005), Dpysl4 (Kimura et al 2011), Sfrp4 (Jacob et al 2012), Dusp1 (Chen et al 2011) and Rcc2 (Grigera et al 2012); and (3) neuronal processes, namely Nmu (Chu et al Regulator of chromosome condensation 2 À2.5*** À2.4*** Sh2d4a SH2 domain containing 4A À2.5* À2.2* Table 2.…”
Section: Expression Of Lrh-1 Target Genes In Lrh-1-kd Micementioning
confidence: 89%
“…Interestingly, peripheral concentrations of EDN1 continued to rise well after the demise of the CL with concentrations of this peptide peaking around the time of estrus. In a later study by Shirasuna et al (63), microdialysis (MDS) lines were implanted into the corpora lutea of naturally cycling cows and the local release of several hormones of interest, including EDN1, determined during spontaneous luteolysis. These authors observed a pulsatile pattern in the local release of EDN1 by the regressing CL, truly suggestive of a regulated, physiological role.…”
Section: Corpus Luteummentioning
confidence: 99%